Gender nonconformity and mental health among lesbian, gay, and bisexual adults: Homophobic stigmatization and internalized homophobia as mediators. (August 2018) - Van Beusekom, Gabriël; Bos, Henny MW; Kuyper, Lisette; Overbeek, Geertjan; Sandfort, Theo GM
We assessed among a sample of 724 Dutch lesbian, gay, and bisexual–identified adults ( M age  = 31.42) whether experiences with homophobic stigmatization and internalized homophobia simultaneously mediated the relation of gender nonconformity with mental health. Results indicated that homophobic stigmatization and internalized homophobia partially mediated the relation between gender nonconformity and mental health. Gender nonconformity was related to more mental health problems via increased experiences with homophobic stigmatization and to less mental health problems because of reduced levels of internalized homophobia. However, the mediated relation of gender nonconformity with mental health via homophobic stigmatization was only significant for men.